ANALISI STRATEGI PEMASARAN INDUSTRI KOPI DI ACEH ( Studi Kasus Solong Kopi Banda Aceh ) - YUDI ARITONA (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
ABSTRACT  This research is entitled "Analysis of the Marketing Strategy of the Coffee Industry in Aceh (Case Study in Solong Coffee Ulee Kareng)". This study aims to find out how to analyze the strategy of maintaining the marketing of the Aceh coffee industry in Solong Coffee Ulee Kareng, how the marketing strategy of the coffee industry in Solong Coffee Banda Aceh when viewed from a SWOT analysis and whether product quality affects customer satisfaction sold by Solong Coffee Ulee Kareng. This research method uses Mix method research, data collection techniques using questionnaires, interviews and observations. Meanwhile, to test the validity of the questionnaire using SPSS version 25. Based on the results of the study, it showed that the quality of the products marketed by Solong Coffee Ulee Kareng met the standards of consumer taste and the results of the data validity test showed that the level of satisfaction and quality indicated an average number of agreeing with the products and services of Solong Coffee Ulee Kareng. Keywords: Marketing, Solong Coffee Ulee Kareng and SWOT Analysis.